Human Resources in Geothermal Development - Fridleifsson, I.B. (United Nations University, Geothermal Training Programme, Reykjavik, Iceland, 1995)
Some 80 countries are potentially interested in geothermal energy development, and about 50 have quantifiable geothermal utilization at present. Electricity is produced from geothermal in 21 countries (total 38 TWh/a) and direct application is recorded in 35 countries (34 TWh/a). Geothermal electricity production is equally common in industrialized and developing countries, but plays a more important role in the developing countries. Apart from China, direct use is mainly in the industrialized countries and Central and East Europe. There is a surplus of trained geothermal manpower in many industrialized countries. Most of the developing countries as well as Central and East Europe countries still lack trained manpower. The Philippines (PNOC) have demonstrated how a nation can build up a strong geothermal workforce in an exemplary way. Data from Iceland shows how the geothermal manpower needs of a country gradually change from the exploration and field development to monitoring and operations.